Can Musculoskeletal Ultrasound Improve Early Detection And Mon- Itoring Of Musculoskeletal Manifestations In Patients With Systemic Lupus Erythematosus? - Luthfiyya Syafiqa Tahany; Sinarty Hartanto (The International Journal of Medical Science and Health Research, 2025)
Introduction: Musculoskeletal manifestations are common in systemic lupus erythematosus (SLE) and significantly impact patient quality of life. Traditional clinical assessments often underestimate joint inflammation. Musculoskeletal ultrasound (MSUS) has emerged as a sensitive, non-invasive imaging modality to detect synovitis, tenosynovitis, and bone erosions in SLE patients. Methods: A comprehensive review of recent clinical trials, cohort studies, and observational research was conducted, focusing on the use of MSUS in detecting and monitoring musculoskeletal involvement in SLE. Studies included grayscale and power Doppler ultrasound protocols assessing multiple joints over various follow-up periods. Results: MSUS consistently detected subclinical synovitis and tenosynovitis, correlating strongly with clinical disease activity indices such as CDAI and DAS28. Persistent power Doppler signals were predictive of structural joint damage and lower remission rates. MSUS also demonstrated utility in monitoring treatment response, with faster reductions in ultrasound inflammation scores observed in patients treated with Janus kinase inhibitors. However, variability in ultrasound protocols and scoring systems was noted across studies. Discussion: MSUS enhances early detection and precise monitoring of musculoskeletal disease activity in SLE, complementing clinical evaluation. Challenges include lack of standardized scanning protocols, operator dependency, and limited correlation with patient-reported outcomes. Standardization efforts like the EULAR-OMERACT scoring system are promising for improving consistency. Conclusion: MSUS is a valuable tool for improving diagnosis, prognosis, and treatment monitoring in SLE-related musculoskeletal disease. Further research and standardization are needed to optimize its integration into routine clinical practice.